Curriculum, sexual and gender diversity: weaving reflections on teacher training (Research, Society and Development, 2020)
The article reflects on the practices of curriculum and teacher training, in the issues inherent to the relations of gender, sexuality and sexual diversity, considering them as themes relevant to the constitution of human subjectivities in contemporary times. Based on this assumption, the present study aims to analyze which curriculum practices concerning issues of gender and sexual diversity permeate teacher training courses, in public higher education institutions in the Identity Territory of Piemonte Norte do Itapicuru, in the State of Bahia. As for the methodological procedures, we opted for the narratives because we understand that such procedures would enable us to have a greater capacity for analysis with respect to the research objective. From the narratives it is possible to show that diversity ends up questioning the curriculum, the school and its pedagogical practice, fostering the need for the themes that contemplate diversity to be ensured in the different times and spaces of doing education. In the fields of teacher training, we understand the need for a review of the curriculum proposals for the undergraduate courses in that Territory, aiming to ensure more space in the curriculum.